NUTRIENT FORTIFICATION OF CHOCOLATE WITH FISH PROTEIN CONCENTRATES AND COLLAGEN FOR BETTER QUALITY - M., MUKESHKANNAN; DHAR, BAHANI; DAS, RUPALI; SINGH, ADITYA; SHARMA, ASWIN (Journal of the Inland Fisheries Society of India, 2026)
The nutritional perception and textural quality of chocolate were improved by incorporating fish protein concentrate (FPC) @ 5% and collagen @ 10% extracted from Rohu fish muscle and scale, respectively. Cocoa powder was replaced with FPC @ 5% in the original composition to enhance the protein content of the chocolate. The protein and moisture content increased steadily with increased FPC concentration, while the ash, lipid, and carbohydrate content decreased. L* (lightness) and b* (yellowness) values of fortified chocolates increased with FPC concentration, whereas a* value gradually decreased. Hardness also improved significantly (p<0.05) in fortified chocolate (5% FPC and 10% collagen). The chocolate with the addition of 5% FPC and 10% fish scale collagen had higher acceptance among panelists, as indicated in sensory evaluation scores, and was recommended for further study.